Determination of Sensitivity of Сlinical Strains of S. aureus Isolated from Patients with Orthopedic and Traumatological Pathology to the Antibacterial Agent “Piophagus” - Liutko , O.B.; Vytrak , K.V.; Mytiakyna , Y.Iu. (TERRA ORTHOPAEDICA, 2020)
Summary. The resistance of clinical microorganism strains isolated in modern hospitals to the corresponding antimicrobial agents, namely antibiotics, is increasing from year to year. Knowledge of the existence of a natural antimicrobial agent that can penetrate the necessary parts of the body and selectively fight pathogens is very desirable in modern medicine. Bacteriophages are one of the most promising alternatives to antibiotics for practical use. In the past, testing of phage therapy has already taken place with the implementation of numerous experimental and practical studies. However, the lack of standardized standards and their planned implementation can explain the infrequent use in practice of this method in the treatment of infectious diseases or postoperative infectious complications at present. A limitation is also the fact that the therapeutic effect after treatment with bacteriophages varies widely and has certain features. This, in general, is associated with the features of different loci when using such drugs and various sensitivity of microorganism strains to a single phage or their combination. Today, there is a better understanding of the pharmacology, immunology, safety and potential of bacterial resistance of phages. There is a growing number of well-performed clinical trials describing the effectiveness of phage therapy. New technologies provide tools to optimize the treatment strategies. The work analyzes the sensitivity of clinical strains of S. aureus isolated from patients with orthopedic and traumatological pathology, and preliminary generalizations are made. The revealed patterns can be used as the results of standardized monitoring of clinical strains of S. aureus in the case of a decrease in the effectiveness of antibiotic therapy in accordance with modern requirements and the transition to phage therapy in practice.